An Antiplatelet Monoclonal Antibody That Inhibits ADP and Epinephrine-Induced Aggregation - Vilella, R; Lozano, T; Mila, J; Borche, L; Ercilla, G; Ordinas, T; Vives, J (Thrombosis and Haemostasis, 1984)
A monoclonal antibody (Mab) named EDU-3, was produced by fusing splenocytes from one Balb/c mouse, immunized with a mixture of platelets and non-T cells from heparinized human peripheral blood, with the HAT-sensitive myeloma line P3-NS1/ l.Ag4.1. By indirect immunofluorescence (IF) it was seen that this Mab reacted with all normal human platelets and bone marrow megakaryocytes, but did not react with lymphoid cells from normal donors, or platelets from Glanzmann’s thrombasthenia (GT) patients. Immunoprecipitation and SDS-PAGE experiments demonstrated that this Mab recognizes an epitope on the IIb-IIIa glycoprotein complex (GPC). EDU-3 inhibited platelet aggregation and release of ATP induced by ADP and epinephrine. Aggregation induced by arachidonic acid, ristocetin and bovine factor VIII were not inhibited by EDU-3. The difference between EDU-3 and other Mab directed against the IIb-IIIa GPC is discussed.
Keywords: Monoclonal antibody-glycoproteins IIb-IIIa; Platelet aggregation